2021
DOI: 10.1002/asi.24559
|View full text |Cite
|
Sign up to set email alerts
|

Are mortgage loan closing delay risks predictable? A predictive analysis using text mining on discussion threads

Abstract: Loan processors and underwriters at mortgage firms seek to gather substantial supporting documentation to properly understand and model loan risks. In doing so, loan originations become prone to closing delays, risking client dissatisfaction and consequent revenue losses. We collaborate with a large national mortgage firm to examine the extent to which these delays are predictable, using internal discussion threads to prioritize interventions for loans most at risk. Substantial work experience is required to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Performance metrics for the study included mean absolute error (MAE), root mean square error (RMSE), and mean absolute percentage error (MAPE) to validate the forecasting performance of our proposed model. These three measures have been widely used in previous studies to examine the difference between actual and forecasted demand (Dai et al, 2022;Goldberg et al, 2022;Mukta et al, 2019). They are calculated as follows:…”
Section: Experiments Design and Performance Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Performance metrics for the study included mean absolute error (MAE), root mean square error (RMSE), and mean absolute percentage error (MAPE) to validate the forecasting performance of our proposed model. These three measures have been widely used in previous studies to examine the difference between actual and forecasted demand (Dai et al, 2022;Goldberg et al, 2022;Mukta et al, 2019). They are calculated as follows:…”
Section: Experiments Design and Performance Metricsmentioning
confidence: 99%
“…Performance metrics for the study included mean absolute error (MAE), root mean square error (RMSE), and mean absolute percentage error (MAPE) to validate the forecasting performance of our proposed model. These three measures have been widely used in previous studies to examine the difference between actual and forecasted demand (Dai et al, 2022; Goldberg et al, 2022; Mukta et al, 2019). They are calculated as follows: MAEgoodbreak=1ni=1n||yigoodbreak−trueyi¯ RMSEgoodbreak=1ni=1nyiyitrue¯2 MAPEgoodbreak=1ni=1nyiyitrue¯yi where yi is the observed hotel demand in week i , and trueyi¯ denotes the forecasted hotel demand in week i .…”
Section: Empirical Studymentioning
confidence: 99%
“…[13] and Goldberg et al [14] each used smoke terms for 13 this purpose, and both found that follow-on machine learning models 14 approached the accuracy of deep learning word embedding models. 15…”
Section: Uses Of Smoke Terms For Text Mining 64mentioning
confidence: 99%